Smart Gate Pass Security Management System Using Random Key Generation (International Journal of Innovative Research in Computer Science & Technology, 2021)
Gate pass management system relates to  the act of security. This system can be used to speed up the  visitor registration which will notify the presence of visitors  in the organisation. This can be used to replace the  traditional visitor registration process. This reduces the  problem of appointments and gathering information about  the visitor via web and android application and this  information is recorded in the database that manages the  data. The Gate pass Management System (GMS) organises  the visitor record and reduces the time of management and  enhances the level of security.
Keywords: OTP; Android Application; Web Application; Gate; Admin and Visitor